2023
DOI: 10.3390/antiox12020243
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Curcumin in Metal Induced Toxicity

Abstract: Metal toxicity poses a potential global threat to the environment and living beings. Their numerous agricultural, medical, industrial, domestic, and technological applications result in widespread distribution in the environment which raises concern on the potential effects of metals in terms of health hazards and environmental pollution. Chelation therapy has been the preferred medical treatment for metal poisoning. The chelating agent bounds metal ions to form complex cyclic structures known as ‘chelates’ to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 197 publications
0
7
0
Order By: Relevance
“…Interestingly, the modulating effect of BA, BX, and UX on SOD activity, in the presence of TCDD, provides avenues for deeper exploration. Some studies have reported that certain compounds can exhibit restorative effects on cellular antioxidant systems when challenged with toxic agents [ 71 ]. The near normalization of SOD levels, especially in the BX co-treatment scenario, warrants further investigations into the underlying molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the modulating effect of BA, BX, and UX on SOD activity, in the presence of TCDD, provides avenues for deeper exploration. Some studies have reported that certain compounds can exhibit restorative effects on cellular antioxidant systems when challenged with toxic agents [ 71 ]. The near normalization of SOD levels, especially in the BX co-treatment scenario, warrants further investigations into the underlying molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional Asian medicinal practices, curcumin has been an extensively employed therapeutic agent attributed to its multifaceted health-promoting characteristics, such as antioxidative, anti-inflammatory, antimutagenic, antimicrobial, and anticancer activities [45] . Being a polyphenol, curcumin exhibits broad biological activity, as it can interact with several cellular signalling pathways, thereby substantiating its extensive health benefits [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Unveiling the Therapeutic Potential Of Curcumin In Hepatic W...mentioning
confidence: 99%
“…The harmful effects of lead (Pb) might vary depending on the extent of exposure, ranging from mild physiological or biochemical abnormalities to serious pathologic disorders where different organs and systems may be damaged or their normal functions changed [31,32]. Pb inhibits the functions of numerous antioxidant defenses; low antioxidant levels can harm the neurological system, liver, kidneys, and reproductive system, among other organ systems [33]. Deposited lead (Pb) in the organ of poultry eventually enter into human's body system causing various health problem.…”
Section: Lead On Poultrymentioning
confidence: 99%